Learning Mathematics With Polya Heuristic Strategies To Increase Students' Critical Thinking Ability - Zulqoidi R. Habibie; Stevanus Budi Waluya; Nuriana Rachmani Dewi (International Conference on Science, Education, and Technology, 2022)
The purpose of this study is to find out the differences in students' critical thinking ability after getting learning with Heuristic Strategies compared to the critical thinking ability of students who get mathematics learning with conventional learning, and how students behave towards mathematics learning with Polya heuristic strategies. This research used experimental methods. The population in this study was all grade VII students of SMPN 1 Muara Bungo, while the sample in this study was randomly selected by two classes. The instruments used in this study are tests of students' mathematical critical thinking ability and attitude scale. The test used is a description type test. The results of this study can be concluded that: (1) the mathematical critical thinking ability of students who get mathematics learning with polya Heuristic Strategies is better than students who get conventional learning models; and (2) siswa be positive towards mathematics learning by using Polya Heuristic Strategies.